Dietary Supplementation With Didancao (Elephantopus scaber L.) Improves Meat Quality and Intestinal Development in Jiaji Ducks - Hu, Chengjun; Gu, Lihong; Li, Mao; Ji, Fengjie; Sun, Weiping; Wang, Dingfa; Peng, Weiqi; Lin, Dajie; Liu, Quanwei; Dai, Haofu; Zhou, Hanlin; Xu, Tieshan (Frontiers in Veterinary Science, 2021)
Didancao (Elephantopus scaber L.) has been used as a traditional herb medicine and exhibited a beneficial role in animal health. This study aimed to investigate the effects of dietary supplementation with Elephantopus scaber L. (E scaber) on growth performance, meat quality, intestinal morphology and microbiota composition in ducks. A total of 480 Jiaji ducks (42-day-old, male: female ratio = 1:1) were randomly assigned to 1 of 4 treatments. There were 6 replicates per treatment, with 20 ducks per replicate. The ducks in the control group (Con) were fed a basal diet; the 3 experimental groups were fed a basal diet supplementation with 30 mg/kg (T1), 80 mg/kg (T2), and 130 mg/kg (T3) E. scaber, respectively. The results showed that no differences were observed in the final body weight, average daily feed intake, and average daily gain among the four groups. Compared with Con group, the feed conversion in the T1 and T2 groups was increased significantly; T3 group was higher than Con group in the concentration of high density lipoprotein-cholesterol (HDL-C). Highest concentration of creatinine (CRE) was observed in T1 group. T2 group was higher than Con group in the contents of Phe, Ala, Gly, Glu, Arg, Lys, Tyr, Leu, Ser, Thr, Asp, and total amino acids in the breast muscle. Moreover, T2 group was higher than Con group in the contents of meat C18:2n-6 and polyunsaturated fatty acid. The concentration of inosine acid (IMP) in T1, T2, and T3 groups was significantly higher than that in Con group. However, Con group was higher than T2 or T3 group in the Zn content. T2 group was lower than Con group in the jejunal crypt depth. T3 group was higher than Con group in the ileal villus height and the ratio of villus height to crypt depth. In addition, T3 group had a trend to significantly increase the abundance of Fusobacteria. Compared to Con group, T1 and T2 groups displayed a higher abundance of Subdoligranulum. Collectively, dietary supplementation with 80 mg/kg E. scaber improves meat quality and intestinal development in ducks.